Practical geriatric oncology - Hurria, Arti; Cohen, Harvey Jay (Cambridge : Cambridge University Press, 2010)
The risk of cancer increases with age, and the number of older adults seeking treatment is increasing dramatically in line with the aging population. The care of older patients differs from that of younger adults because of differences in the biology of the tumor, age-related differences in host physiology, comorbidity burden and psychosocial issues, which might impact the efficacy and side effects of cancer therapy. Practical Geriatric Oncology is a comprehensive, evidence-based text that synthesizes the growing literature in this field and provides practical guidelines to the care of older adults with cancer. Coverage includes patient assessment, management of solid tumors and hematologic malignancies, the impact of age on the pharmacology of cancer therapy, surgical oncology and radiation oncology in the older adult, symptom management and supportive care. In addition to serving as core reading for oncologists and hematologists, the book will also be a useful work for other healthcare professionals who provide oncology care, including surgeons, radiation oncologists, palliative care doctors, primary care providers, geriatricians and nurses.
Part III. Management of hematologic malignancies in older adults: 15. Management of myelodysplasia in older adults / Heidi D. Klepin and Bayard L. Powell -- 16. Management of chronic leukemia in older adults / Martha Wadleigh and Richard Maury Stone -- 17. Management of acute myeloid leukemia in older adults / Arati V. Rao and Joseph O. Moore -- 18. Hematopoietic cell transplantation in older adults / Andrew S. Artz and William B. Ershler -- 19. Management of non-Hodgkin's lymphoma in older adults / Anne H. Blaes and Vicki A. Morrison -- 20. Management of myeloma in older adults / Amrita Y. Krishnan -- Part IV. Symptom management and supportive care of older adults: 21. Optimizing quality of life in older adults with cancer / Alice B. Kornblith and Mark T. Hegel -- 22. Optimizing functional status in older adults with cancer / Gijsberta van Londen and Stephanie Studenski -- 23. The myeloid growth factors in older adults with cancer / Gary H. Lyman -- 24. Erythropoiesis-stimulating agents in older adults with cancer / Matthew S. McKinney and Jeffrey Crawford -- 25. Management of depression and anxiety in older adults with cancer / Mark I. Weinberger, Christian J. Nelson, and Andrew J. Roth -- 26. Management of pain in older adults with cancer / Anthony Nicholas Galanos, Katya Elbert-Avila, Leslie J. Bryan -- 27. Management of fatigue in older adults with cancer / Tami Borneman, Virginia Sun, and Betty Ferrell -- 28. Management of dyspnea in older adults with cancer / Amy P. Abernethy, Jane L. Wheeler, and David C. Currow -- 29. Management of the gastrointestinal side effects of therapy in older adults with cancer / Laura Raftery, Stephen A. Bernard, and Richard M. Goldberg.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Geriatric oncology